Reaching the first 90 in the Democratic Republic of the Congo: a programme to optimise HIV case finding through intensified index testing. Issue 1 (April 2020) - Dane, Sarina; Jha, Ayan; Dibulundu, Desire; Ilunga, Yves; Tchissambou, Tania; Ngalamulume-Roberts, Bibola; Hartsough, Kieran; Malele Bazola, Faustin; Morrison, Ellen; Michaels-Strasser, Susan; Soares Linn, Juliana
Abstract: Background: To meet the first aim of the UNAIDS 90-90-90 targets, to help end the global HIV epidemic, 90% of people living with HIV should know their status by 2020. In the Democratic Republic of the Congo (DRC), however, UNAIDS estimates that less than 60% of people living with HIV know their status. To improve targeted HIV testing in Kinshasa and Haut-Katanga provinces of DRC, ICAP at Columbia University, New York, USA, launched an intensive index-testing programme in October, 2017. Here, we describe the programme and report testing yields before and after the intervention. Methods: Our programme increased efforts to elicit information on sexual partners from people who newly test HIV positive or who were receiving antiretroviral therapy (index clients). All index clients were counselled on options for partner notification and tracing, including using peer counsellors who can anonymously notify and test past sexual partners in the community or provide referral to health facilities. We recorded the number of people referred by index clients and describe HIV testing yield (the proportion of people referred by index clients who tested HIV positive) for both male and female clients older than 15 years. We used χ 2 tests to compare the testing yield at the start of the intervention to that 10 months after the start of programme implementation. Findings: Between Oct 1, 2017, and Sept 30, 2018, 2167 male index clients referred 2624 adult female partners (1·2 contacts per index client) of whom 770 (29·3%) tested HIV-positive; 5135 adult female index clients referred 2593 male partners (0·5 contacts per client) of whom 866 (33·4%) were HIV positive. HIV testing yield increased over the course of implementation. At the start of implementation (Oct 1 to Nov 30, 2017, a total of 60 days), 507 adult female partners of index clients were tested for HIV with a testing yield of 12% and 386 adult male partners were tested with a yield of 15%. Between August 1 and Sept 30, 2018 (a total of 60 days), 396 adult female partners were tested with a yield of 38·4% (pre vs post, p<0·0001) and 547 adult male partners were tested with a yield of 41·7% (p<0·0001). Interpretation: These results show the importance of index testing and partner notification in finding people who are living with HIV but unaware of their status. Identification of a client's sexual partners in the HIV testing service and conducting tracking and community-based HIV testing can improve HIV testing yield. Funding: CDC and PEPFAR